FATAL HEMORRHAGE FROM VARICOSE VEIN AFTER MINOR TRAUMA (Journal of Forensic Medicine & Toxicology, 2018)
A minor trauma to varicose vein can result in sudden death due to excessive uncontrollable hemorrhage. One such incident happened where one school teacher while moving in the class got minor injury to leg which led to her death due to bleeding from injured varicose vein and scarred skin.
Keywords: minor trauma; udden death; varicose vein trauma; sclerosis of vessels and trauma